When Tourism is Too Much. Tourist Carrying Capacity of the Vesuvius National Park - Agovino, Massimiliano; Corbisiero, Fabio; Marotta, Ilaria (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
The territory of the Vesuvius National Park is a concentrate of natural riches, history of volcanology, breathtaking landscapes, centuries-old crops, and traditions that make the Vesuvius area one of the most fascinating and one of the most visited places in the world. The attractiveness of the Park generates serious congestion problems especially in high season, compromising the natural balance of the area. To assess the degree of balance between the environmental and economic sustainability of the Vesuvius National Park, we propose a Tourist Carrying Capacity Index (TCCI) based on the years 2019-2020. Unlike the previous analyses, we obtain a range of TCC to identify an area of compromise between environmental and socio-economic sustainability of tourism. The results suggest management interventions capable of spreading the tourist flow in a homogeneous way during all months of the year in this area.